Smoke-free hospitality environments and cognitive health: A population-based study in the United States - Lucie Kalousová (Preventive Medicine Reports)
Introduction: Cigarette smoking is among the largest risk factors for cognitive decline in later life. This study examines the associations between hospitality smoke-free coverage in the US and the prevalence of self-rated cognitive function decline and disparities therein. Methods: I use the repeated cross-sectional Behavioral Risk Factor Surveillance data collected between 2017 and 2022 from a sample of Americans 45 years and older and estimate logistic regression models predicting self-rated cognitive function decline by calculated smoke-free hospitality coverage in restaurants and bars. Results: Fully adjusted models indicate a marginally statistically significant 0.16 percentage point reduction [CI −0.35 to 0.02] in the probability of self-rated cognitive function decline for a 10 % increase in the smoke-free bar coverage. The effect is statistically significant and larger for women, a 0.29 [CI −0.50 to −0.01] percentage point decrease, and for non-smokers, a 0.35 [CI −0.56 to −0.15] percentage point decrease. I do not find a parallel effect of smoke-free restaurant laws and I find no effect of either law on self-rated cognitive function decline-related limitations in daily life for either hospitality law. Conclusions: The findings suggest that smoke-free bar laws could play a role in preventing cognitive decline among older adults in the United States. Effective public health strategies against cognitive decline should include both targeted and broad-based policy measures.